Ultraviolet curing organic silicon and UV adhesive composition for difficult-to-adhere materials
Through the rearrangement reaction of linear phosphorus chloride eye catalyst and acrylic modified polydimethylsiloxane, combined with acrylate monomer and photoinitiator, the problem of insufficient bonding strength of UV glue to low-surface energy substances is solved, and the problem of UV glue is achieved. The preparation of high molecular weight ultraviolet cured silicone has excellent bonding strength and environmental protection, and is suitable for the heat-resistant electronic and electrical industry.
Patent Information
- Application Number
- CN202411502653.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The existing UV glues are insufficient to bond strength to low-surface energy substances (such as PE, PP, PET, POE, etc.), and the high temperature of traditional hot melt adhesives limits their application in the heat-resistant electronic and electrical industry, and the methacryloyloxy group is Terminal polydimethylsiloxane is expensive and easy to hydrolyze and produces malodorous substances.
Linear phosphorus chloride eye catalyst and acrylic modified polydimethylsiloxane are used to rearrange the reaction to generate high molecular weight ultraviolet cured silicone, combined with acrylate monomer and free radical photoinitiator to form an excellent bonding strength UV glue.
Excellent bonding strength to low-surface energy substances is achieved, high-temperature processes and foul-odor substances are avoided, and process complexity and cost are reduced.
Smart Images

Figure BDA0005103004740000021 
Figure BDA0005103004740000022 
Figure BDA0005103004740000031
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ultraviolet (UV) curing adhesives, and in particular relates to a UV adhesive composition having good adhesion and bonding strength to difficult-to-bond materials. Background Art
[0002] The bonding of low surface energy materials (such as PE, PP, PET, POE, etc.) has always been a difficult problem and pain point in the adhesive industry. These materials are generally considered to be difficult to bond. Although hot melt adhesives have been developed for these low surface energy materials, hot melt adhesives themselves are thermoplastic resins, and their use temperature is difficult to exceed 100°C, which greatly limits their application in the electronic and electrical industry that requires heat resistance.
[0003] UV glue (ultraviolet curing adhesive) is increasingly favored by the industry because of its fast curing speed, energy saving and environmental protection, especially in the assembly line of electronic components. UV glue can be cured in seconds, the assembly speed of the production line can be greatly accelerated, and the use of UV glue can greatly improve production efficiency. The oligomers used in UV glue usually have more than two functional groups, can form a cross-linked network, and have good heat resistance. Therefore, UV glue is used for potting and bonding of many electronic components. However, UV glue composed of ordinary polyurethane acrylate compounds does not have sufficient bonding strength for low surface energy materials, and the cationic curing system of alicyclic epoxy resin does not have good adhesion to these materials. To obtain good bonding strength, the surface of the material must be physically treated (mechanical grinding and roughening of the surface, short-wavelength ultraviolet irradiation, corona, plasma treatment, etc.) or chemically treated (silane coupling agent, primer, etc.). Sometimes, even if the surface treatment is performed, sufficient bonding strength cannot be obtained. These treatment projects are not only time-consuming and labor-intensive, but also increase the process cost and pollute the working environment. Therefore, the industry has been looking for a UV glue that can be directly applied without surface treatment.
[0004] Japanese patent (Japanese Patent No. 2008-31307) discloses an organosiloxane composition that can be cured by ultraviolet light, which has relatively good bonding strength to PET, PBT, PC, ABS, and LCP (liquid crystal polymer). The synthesis method is to use terminal hydroxyl polydimethylsiloxane (107 silicone oil) and aminosilane coupling agent for dealcoholization reaction, and then react with 2-isocyanatoethyl methacrylate to form methacryloyloxy-terminated polydimethylsiloxane, and combine with some acrylate monomers that are compatible with organosilicon to form UV glue. The shear strength of PET / PET can reach 2.8MPa, which basically meets the requirements of bonding strength for most applications. However, the price of this 2-isocyanatoethyl methacrylate monomer is very expensive, resulting in the high price of the synthesized methacryloyloxy-terminated polydimethylsiloxane, which can only be used for high-end applications. In addition, this methacryloyloxy-terminated polydimethylsiloxane has a fatal flaw. After long-term storage, it will undergo trace hydrolysis to produce a foul-smelling substance. Customers will feel very uncomfortable during use, and no effective solution has been found so far. Summary of the invention
[0005] The object of the present invention is to provide an ultraviolet curing organic silicone adhesive for difficult-to-bond materials (such as PE, PP, PET, POE, etc.).
[0006] The technical solution to achieve the purpose of the present invention is:
[0007] In a first aspect, the present invention provides a UV-curable silicone, which is an acrylic modified polydimethylsiloxane having the following structure:
[0008]
[0009] Wherein n=an integer from 40 to 2000.
[0010] In a second aspect, the present invention provides a method for synthesizing the ultraviolet curable silicone according to the first aspect, comprising:
[0011] (1) a step of performing a hydrosilylation reaction with a hydrogen-containing double-capped agent (tetramethyldisiloxane) and 4-vinylcyclohexene oxide in the presence of a platinum catalyst to generate a double-capped agent having an epoxy group at each end,
[0012]
[0013] (2) a step of subjecting a double-capping agent having an epoxy group at each end and an excess of acrylic acid to a ring-opening esterification reaction in the presence of a ring-opening esterification catalyst to obtain a double-capping agent having a hydroxyl group and an acryloxy group at each end,
[0014]
[0015] (3) subjecting a double-capping agent having one hydroxyl group and one acryloyloxy group at each end to an esterification dehydration reaction with excess acrylic acid in the presence of a cyclohexane water-carrying agent and an acidic catalyst to generate a double-capping agent having two acryloyloxy groups at each end,
[0016]
[0017] (4) a step of rearranging a double-capping agent having two acryloyloxy groups at each end with polydimethylsiloxane in the presence of a linear chlorinated phosphine catalyst to obtain a high molecular weight acrylic acid-modified polydimethylsiloxane, i.e., ultraviolet curing silicone.
[0018]
[0019] Preferably, in order to prevent acrylic acid from self-polymerizing during the ring-opening esterification and esterification dehydration reactions, a free radical inhibitor needs to be added in both the ring-opening esterification and esterification dehydration reactions, and the added amount is 0.01% to 1% of the total mass of the reactants.
[0020] Specifically, the free radical inhibitor is any one or more of p-methoxyphenol (MeHQ), hydroquinone (HQ), and 2,6-di-tert-butyl-4-methylphenol (BHT).
[0021] Preferably, the ring-opening esterification catalyst is selected from tertiary amines and quaternary ammonium salts, and is commonly used any one of triethylamine, N,N-dimethylbenzylamine, N,N-dimethylaniline, trimethylbenzylammonium chloride, triphenylphosphine, triphenylantimony, chromium acetylacetonate, chromium isooctanoate, stannous octoate, tetraethylammonium bromide, etc., and its usage is 0.1% to 5.0% of the reactants.
[0022] Preferably, the acidic catalyst for the esterification dehydration reaction is selected from any one of concentrated sulfuric acid, sodium bisulfate, methanesulfonic acid, toluenesulfonic acid, trifluoromethanesulfonic acid, a strongly acidic ion exchange resin and a solid superacid, preferably any one of methanesulfonic acid, trifluoromethanesulfonic acid, a strongly acidic ion exchange resin and a solid superacid, and the added amount is 0.1% to 5.0% of the total mass of the reactants.
[0023] Preferably, the amount of linear phosphonium chloride catalyst added is 0.005-1.0% of the total amount of reactants.
[0024] Preferably, after the rearrangement reaction is completed, a passivating agent is used to inactivate the linear phosphonium chloride, and the amount of the passivating agent added is 1.1 to 4.0 times the amount of the linear phosphonium chloride added.
[0025] Specifically, the passivating agent can be selected as follows: First, amine compounds, such as triethylamine, propylamine, triethylnonylamine, hexamethyldisilazane, hexamethylcyclotrisilazane, etc. Second, lithium salts, n-butyl lithium n-hexane solution, hexamethyldisilazane lithium salt, trimethylsiloxy lithium, polydimethylsiloxane alkali glue of lithium hydroxide, etc. can be selected. Third, epoxy compounds, compounds containing more than one epoxy group in the molecule such as propylene oxide, glycidyl ether, bisphenol A diglycidyl ether, phenyl glycidyl ether, cyclohexene oxide, etc. can be selected. Fourth, salts of magnesium, aluminum, calcium, zinc, barium, and sodium, magnesium oxide, magnesium carbonate, magnesium hydroxide, aluminum oxide, zinc oxide, barium carbonate, sodium carbonate, etc. are selected. Triethylamine and hexamethyldisilazane are preferred.
[0026] In a third aspect, the present invention provides a UV adhesive composition for difficult-to-bond materials comprising the UV-curable silicone described in the first aspect, which comprises, by weight, 100 parts of UV-curable silicone, 10 to 80 parts of acrylate monomers and 0.5 to 5.0 parts of free radical photoinitiator.
[0027] Preferably, the acrylate monomer is selected from any one or two of isobornyl acrylate (IBOA), cyclohexyl acrylate, tetrahydrofuranyl acrylate (THFA), tricyclodecyl acrylate, dicyclopentadiene acrylate, acryloyl morpholine (ACMO) and N,N-dimethylacrylamide (DMAA), preferably isobornyl acrylate, tetrahydrofuranyl acrylate (THFA), acryloyl morpholine (ACMO) and N,N-dimethylacrylamide (DMAA).
[0028] Preferably, the free radical photoinitiator is selected from 2-hydroxy-2-methylphenylacetone (Darocure 1173), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L), a mixture of 2,4,6-trimethylbenzophenone and 4-methylbenzophenone, benzoin dimethyl ether, benzophenone (BP), 1-hydroxy-cyclohexyl benzophenone, α,α′-ethoxyacetophenone (DEAP) or α-aminoalkylphenone, or a mixture of several thereof.
[0029] Preferably, based on the consideration of water resistance, the UV adhesive composition for the difficult-to-bond material may also be added with various epoxy silane coupling agents, titanate coupling agents, zirconate coupling agents, aluminate coupling agents, etc.
[0030] Preferably, the UV adhesive composition for difficult-to-bond materials further includes hydrophobic silica.
[0031] Compared with the prior art, the advantages of the present invention are:
[0032] (1) The present invention adopts a linear chlorinated phosphinothricin catalyst, and carries out a rearrangement reaction between the bisacryloxy double-capped and polydimethylsiloxane in the presence of the linear chlorinated phosphinothricin catalyst to obtain a high molecular weight UV-cured silicone. The reaction conditions are mild, the reaction speed is relatively fast, and no siloxane ring body is produced during the entire reaction process, and the volatile matter is extremely small, which well solves the problems of low activity of the target product of the traditional acid-catalyzed equilibrium reaction, low content of effective ingredients, residual low-boiling substances and many ring bodies. The cumbersome process of high vacuum and long-term high-temperature devolatilization with nitrogen gas in the later stage of the reaction is eliminated.
[0033] (2) The UV-curable organic silicone adhesive composition of the present invention has excellent bonding strength to low surface energy materials (such as PE, PP, PET, POE, etc.). DETAILED DESCRIPTION
[0034] The present invention is described in detail below with reference to the embodiments.
[0035] An effective method for connecting (meth)acryloyloxy groups to both ends of polydimethylsiloxane is to utilize the hydrosilylation reaction. First, terminal hydrogen-containing silicone oil and a bifunctional compound having an allyl group and an epoxy group or a hydroxyl group are subjected to hydrosilylation to generate a polydimethylsiloxane having a terminal epoxy group or a hydroxyl group structure. The polydimethylsiloxane having a terminal epoxy group or a hydroxyl group structure is then reacted with (meth)acrylic acid to introduce the (meth)acryloyloxy groups into the terminal groups of the polydimethylsiloxane, thereby imparting ultraviolet curing properties.
[0036] The purpose of the present invention is to connect two acryloyloxy functional groups to each end of polydimethylsiloxane, so that its UV curability is better than that of polydimethylsiloxane with one acryloyloxy structure at each end. In particular, for high molecular weight polydimethylsiloxane, if the end group has only one acryloyloxy group, the UV curability will be weakened due to the very small proportion of UV curable functional groups. If the end group has two acryloyloxy groups, the UV curability will be greatly improved, the cross-linking density will be higher, and the bonding strength will be correspondingly greater.
[0037] If a terminal hydrogen silicone oil (high molecular weight terminal hydrogen silicone oil) with extremely low hydrogen content is directly used as the initial reaction raw material and 4-vinyl cyclohexene oxide is used to synthesize a high molecular weight terminal functional silicone oligomer, the SiH content is too low, resulting in an incomplete silane addition reaction, that is, less active substances are connected to the terminal group, which is not conducive to the next step of the reaction to obtain a silicone oligomer with good UV curability. In addition, 4-vinyl cyclohexene oxide and low hydrogen silicone oil (that is, high molecular weight terminal hydrogen silicone oil) have poor compatibility, and the reaction is difficult to carry out. The common method in the industry is to use the silane addition reaction to synthesize a low molecular weight terminal active polydimethylsiloxane, and then extend the chain through the D4 equilibrium polymerization reaction to obtain a high molecular weight terminal active polydimethylsiloxane. However, there are disadvantages such as low equilibrium conversion rate, the need to remove low boiling point residues and small molecular ring bodies after the reaction is completed, poor yield, and complicated process.
[0038] The synthesis method of the present invention is to first synthesize a double-capping agent containing two acryloyloxy groups at both ends, and then carry out a rearrangement reaction with polydimethylsiloxane in the presence of a linear chlorinated phosphinate catalyst to obtain a high molecular weight ultraviolet curing polydimethylsiloxane. During the entire reaction process, no siloxane ring body is generated, and the volatile matter is extremely small, which well solves the problems of low activity, low effective component content, residual low boiling point substances and large number of ring bodies of the target product of the traditional acid-catalyzed equilibrium reaction. After the reaction is completed, a passivating agent is used to inactivate the linear chlorinated phosphinate.
[0039] Synthetic UV-curable silicone is combined with acrylate monomers, free radical photoinitiators, coupling agents, and hydrophobic silicone to form a UV adhesive with excellent bonding strength to low surface energy materials.
[0040] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0041] The following is a detailed introduction to the synthesis and formulation examples of UV-curable polydimethylsiloxane.
[0042] Synthesis of epoxy double capping agent.
[0043] Into a three-necked glass flask equipped with an oil bath and a condenser, 160 g of 4-vinyl cyclohexene oxide and 0.01 g of chloroplatinic acid were added, the temperature was raised to 70°C with stirring, and 100 g of hydrogen-containing double-capped agent (1,1,3,3-tetramethyldisiloxane) was added dropwise. The addition was completed within one hour, and then the temperature was raised to 80°C and the reaction was continued for 4 hours. The unreacted hydrogen-containing double-capped agent was removed in vacuo to obtain a colorless, transparent double-capped agent containing an epoxy group at each end (referred to as epoxy double-capped agent) with a molecular weight of 382.7.
[0044] Synthesis of hydroxyacryloyloxy double capping agent.
[0045] Into a three-necked glass flask equipped with an oil bath and a condenser, 100 g of epoxy double-capping agent, 0.5 g of tetraethylammonium bromide, and 0.05 g of MeHQ free radical inhibitor were added. The temperature was raised to 70°C with stirring, and 50 g of acrylic acid was added dropwise within one hour. The temperature was then raised to 80°C and the reaction was continued for 6 hours. Excessive sodium carbonate was added to neutralize the residual acrylic acid and tetraethylammonium bromide. The precipitate was filtered, washed with water several times, and then vacuum dried to obtain a light yellow transparent double-capping agent containing a hydroxyl group and an acryloyloxy group at each end (referred to as hydroxyacryloyloxy double-capping agent) with a molecular weight of 526.8.
[0046] Synthesis of bisacryloyloxy double capping agent.
[0047] Add 100g of hydroxyacryloxy double-capping agent, 0.05g of MeHQ free radical inhibitor, 0.05g of BHT free radical inhibitor, 0.5g of trifluoromethanesulfonic acid, and 100g of cyclohexane water-carrying agent into a three-necked glass flask with an oil bath and a condenser device, stir and heat to 85°C and reflux, add 35g of acrylic acid dropwise, and complete the addition within one hour. The water brought out is regularly released with a separatory tube, and the amount of water retained in the separatory tube is carefully observed until no more excess water is distilled out, and the reaction is considered complete. Cool to room temperature, add excess sodium carbonate to neutralize the residual acrylic acid and trifluoromethanesulfonic acid, precipitate and filter, wash with water several times, and then vacuum dry to obtain a light yellow transparent double-capping agent with two acryloyloxy groups at each end (referred to as bisacryloxy double-capping agent), with a molecular weight of 634.9.
[0048] Modified silicone synthesis example-1.
[0049] In a three-necked glass flask with an oil bath and a condenser, add 85g of polydimethylsiloxane with a viscosity of 1000mPas and 0.1g of linear phosphine chloride catalyst, stir and heat to 80°C under nitrogen protection, gradually add 10g of double-capping agent bisacryloxy, and complete the addition within one hour, then heat to 110°C and continue to react for 4h, cool to room temperature, add 0.2g of triethylamine passivator, and obtain colorless and transparent polydimethylsiloxane with two acryloxy groups at each end, i.e., UV-curable silicone, with a molecular weight of about 6420. The product is named Modified Silicone Synthesis Example-1.
[0050] Modified silicone synthesis example-2.
[0051] In a three-necked glass flask with an oil bath and a condenser, add 1000g of polydimethylsiloxane with a viscosity of 500mPas and 0.5g of linear chlorinated phosphine catalyst, stir and heat to 80°C, gradually add 19g of double-capping agent bisacryloxy, and complete the addition within half an hour, then heat to 110°C and continue to react for 4h, cool to room temperature, add 1.0g of hexamethyldisilazane passivator, and obtain colorless and transparent polydimethylsiloxane with two acryloxy groups at each end, i.e., ultraviolet curing silicone, with a molecular weight of about 36800. The product is named Modified Silicone Synthesis Example-2.
[0052] The UV curable silicone prepared above is compounded with acrylate monomers and the like to prepare a UV adhesive composition. The specific formula is shown in Table 1.
[0053] Table 1
[0054] Example-1 Example-2 Example-3 Example-4 Comparative Example-1 Comparative Example-2 Comparative Example-3 Comparative Example-4 Modified silicone synthesis example-1 100 100 Modified silicone synthesis example-2 100 100 100 Baojun Chemical 2900 100 Zhongshan Qianyou 3001 100 100 IBOA 40 40 40 30 40 40 40 DMAA 5 5 5 ACMO 5 5 5 5 THFA 5 10 5 TS720 20 25 20 15 R972 20 15 15 15 Darocure1 173# 2.0 2.0 2.0 2.0 2.0 2.0 2.0 2.0 TPO-L 1.0 1.0 1.0 1.0 1.0 1.0 1.0 1.0 KBM403 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 KBM5103 0.5 0.5 0.5 0.5 0.5 05 0.5 0.5 Shear strength(MPa) PE / PE 0.9 1.5 1.3 1.5 0.4 03 0.4 0.5 PP / PP 1.5 2.6 2.5 3.3 1.1 0.5 0.9 1.0 PET / PET 1.9 3.2 3.5 3.7 1.0 2.5 2.7 2.6 POE / POE 24 4.1 45 4.9 0.9 0.9 1.1 12
[0055] Note: TS720 is Cabot hydrophobic silica from the United States; R972 is Evonik hydrophobic silica from Germany; KBM403 is Shin-Etsu γ-glycidyloxypropyl trimethoxysilane from Japan; KBM5103 is Shin-Etsu 3-(acryloyloxy)propyl trimethoxysilane from Japan; Baojun Chemical 2900 is a polyurethane type acrylate oligomer with good bonding strength to PET film; Zhongshan Qianyou 3001 is a polyurethane type acrylate oligomer with good bonding strength to PET film; IBOA is isobornyl acrylate; DMAA is N,N-dimethylacrylamide; ACMO is acryloylmorpholine; THFA is tetrahydrofuran acrylate; PE is polyethylene; PP is polypropylene; PET is polyethylene terephthalate; POE is polyolefin elastomer.
[0056] Preparation of shear strength test piece: Wipe the surface of the test piece with alcohol to remove the oil and dust on the surface. Fix it with a butterfly clip after gluing, and then cure it with ultraviolet light. The ultraviolet light dose is 1000mJ / cm on both sides. 2 , place at room temperature for 30 minutes to test the shear strength. The test method is in accordance with GB / T 7124-2008.
[0057] According to Table 1, by comparing Examples 1 to 4, it is found that the UV-curable silicone UV adhesive compounded with acrylate monomers of the present invention shows good bonding strength for PE, PP, PET, POE, etc. However, Comparative Example 1 uses a single UV-curable polydimethylsiloxane without compounding with acrylate monomers, and its bonding strength is relatively low. Comparative Examples 2 to 4 use commercially available polyurethane acrylate oligomers compounded with UV adhesives that have good bonding strength to PET films. Although they have good adhesion to PET films, their bonding strength to low surface energy materials such as PE, PP, POE, etc. is very low and does not meet practical requirements.
Claims
1. A UV-curable silicone, characterized in that: It is an acrylic modified polydimethylsiloxane having the following structure: Wherein n=an integer from 40 to 2000.
2. The method for synthesizing ultraviolet curable silicone according to claim 1, characterized in that: include: (1) a step of performing a hydrosilylation reaction on a hydrogen-containing double-capping agent and 4-vinyl cyclohexene oxide in the presence of a platinum catalyst to generate a double-capping agent having an epoxy group at each end, (2) a step of subjecting a double-capping agent having an epoxy group at each end and an excess of acrylic acid to a ring-opening esterification reaction in the presence of a ring-opening esterification catalyst to obtain a double-capping agent having a hydroxyl group and an acryloxy group at each end, (3) subjecting a double-capping agent having one hydroxyl group and one acryloyloxy group at each end to an esterification dehydration reaction with excess acrylic acid in the presence of a cyclohexane water-carrying agent and an acidic catalyst to generate a double-capping agent having two acryloyloxy groups at each end, (4) a step of rearranging a double-capping agent having two acryloyloxy groups at each end with polydimethylsiloxane in the presence of a linear chlorinated phosphine catalyst to obtain a high molecular weight acrylic acid-modified polydimethylsiloxane, i.e., ultraviolet curing silicone.
3. The method according to claim 2, characterized in that In both the ring-opening esterification and the esterification dehydration reaction, a free radical inhibitor is added, and the amount added is 0.01% to 1% of the total mass of the reactants.
4. The method according to claim 2, characterized in that The catalyst for the ring-opening esterification reaction is selected from tertiary amines and quaternary ammonium salts, and is commonly used any one of triethylamine, N,N-dimethylbenzylamine, N,N-dimethylaniline, trimethylbenzylammonium chloride, triphenylphosphine, triphenylantimony, chromium acetylacetonate, chromium isooctanoate, stannous octoate, and tetraethylammonium bromide, and its usage is 0.1% to 5.0% of the reactants.
5. The method according to claim 2, characterized in that The acidic catalyst for the esterification dehydration reaction is selected from any one of concentrated sulfuric acid, sodium bisulfate, methanesulfonic acid, toluenesulfonic acid, trifluoromethanesulfonic acid, strongly acidic ion exchange resin and solid super acid, preferably any one of methanesulfonic acid, trifluoromethanesulfonic acid, strongly acidic ion exchange resin and solid super acid, and its addition amount is 0.1% to 5.0% of the total mass of the reactants.
6. The method according to claim 2, characterized in that The amount of linear phosphonium chloride catalyst added is 0.005-1.0% of the total amount of reactants.
7. The method according to claim 2, characterized in that After the rearrangement reaction is completed, a passivating agent is used to inactivate the linear phosphonium chloride, and the amount of the passivating agent added is 1.1 to 4.0 times the amount of the linear phosphonium chloride added.
8. A UV adhesive composition for difficult-to-bond materials, characterized in that: The invention comprises, by weight, 100 parts of the ultraviolet curing silicone as claimed in claim 1, 10 to 80 parts of acrylate monomers and 0.5 to 5.0 parts of free radical photoinitiator.
9. The composition according to claim 8, characterized in that The acrylate monomer is selected from any one or two of isobornyl acrylate (IBOA), cyclohexyl acrylate, tetrahydrofuranyl acrylate (THFA), tricyclodecyl acrylate, dicyclopentadiene acrylate, acryloyl morpholine (ACMO) and N,N-dimethylacrylamide (DMAA), preferably isobornyl acrylate, tetrahydrofuranyl acrylate (THFA), acryloyl morpholine (ACMO) and N,N-dimethylacrylamide (DMAA).
10. The composition according to claim 8, characterized in that The free radical photoinitiator is selected from 2-hydroxy-2-methylphenylacetone (Darocure 1173), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L), a mixture of 2,4,6-trimethylbenzophenone and 4-methylbenzophenone, benzoin dimethyl ether, benzophenone (BP), 1-hydroxy-cyclohexyl benzophenone, α,α′-ethoxyacetophenone (DEAP) and α-aminoalkylphenone. One or a mixture of several.
Citation Information
Patent Citations
Photocurable organopolysiloxane composition
JP2008031307A
Ultraviolet curing organic silicon release agent
CN114015053A
UV peelable adhesive and preparation method thereof
CN117210185A
Laminated glass and display device using the same
JP2013107814A
Cited By
Epoxy glue for chip multi-surface encapsulation protection, preparation method thereof and wafer encapsulation structure
CN120737781A
Epoxy adhesive for multi-faceted packaging protection of chips, preparation method thereof and wafer packaging structure
CN120737781B